Religious Politeness in Subtitling: A Brown and Levinson Analysis of Kiai’s Utterances in Sang Kiai - Ikke Dewi Pratama (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
This research analyzes the realization of politeness strategies in the Indonesian – English subtitles of Sang Kiai movie, focusing on how authority and power relations between Kiai Hasyim Asy’ari and his santri at Tebu Ireng Islamic boarding school, are represented in translation. Using a descriptive design with an ethnographic approach, the study analyzes 49 utterances drawn from the interactions between Kiai Hasyim Asy’ari and his santri in the source and target texts using Brown and Levinson’s politeness framework. The findings reveal that there are three recurrent patterns: (1) preservation of politeness strategy, (2) shift in politeness strategy, and (3) preservation of strategy with sub-strategic shift. The dominant pattern is preservation of politeness strategy, particularly in the use of bald on record and positive politeness, which reflects the institutional authority of Kiai Hasyim Asy’ari. The study shows that the subtitling largely maintains the power asymmetry inherent in pesantren discourse, suggesting that authority works as a key basis in the realization and translation of politeness strategies.